Air conditioning energy profile and intensity index for retrofitted mosque building: a case study in Malaysia - Hussin, Azman; Lim, Chin Haw; Salleh, Elias (Universiti Putra Malaysia Press, 2019)
Mosques generally consume far lesser energy than other types of buildings owing to their functional and operational characteristics. Since an effective energy management with a proper handling of the air-conditioning system can offer benefits such as the reduction of energy consumption as well as contributing to a sustainable development of the mosque, this paper has therefore presented a field case study on the energy usage and optimization strategies from a few selected retrofitted air-conditioned mosques in Penang, Malaysia. The results derived from the mosque samples (n=5) had not only shown a high energy consumption of the current air-conditioning system, the field evaluation at the Penang State Mosque (G5) was also revealed to have demonstrated a very high Energy Intensity Index (323 kWh/m2/yr.) and non-compliance to the MS Standards. As such, this study had proposed a few short and long term energy savings strategies, which can be implemented by the management committee of the mosque in not only in providing optimum thermal comfort for the worshippers but also without incurring the high energy costs.